Using Unnatural Protein Fusions to Engineer a Coenzyme Self-Sufficiency System for D-Phenyllactic Acid Biosynthesis in Escherichia coli - Qin, Zhao; Wang, Dan; Luo, Ruoshi; Li, Tinglan; Xiong, Xiaochao; Chen, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
The biosynthesis of D-phenyllactic acid (D-PLA), a broad-spectrum antimicrobial natural compound, is often affected by insufficient supply and regeneration of cofactors and redox equivalents, leading to high production cost and difficulty in industrialization. In this study, D-lactate dehydrogenase (D-LDH) and glycerol dehydrogenase (GlyDH) co-expression system was constructed to achieve coenzyme NADH self-sufficiency and sustainable production of D-PLA. Using glycerol and phenylpyruvate (PPA) as co-substrate, the engineered strain CP201 harboring LfD-LDH-BmGlyDH produced 3.95 g/L D-PLA with a yield of 0.78 g/g PPA. In order to further improve the yield of D-PLA, flexible linkers with sequence of (GGGGS)1, (GGGGS)2, (GGGGS)3 and (GGGGS)6 were synthesized for D-LDH and GlyDH fusion protein construction. Under the optimal conditions, 5.87 g/L D-PLA was produced in engineered strain CP304 harboring LfD-LDH-l6-BmGlyDH with a yield of 0.97 g/g PPA, which was 59.3% increased compared to the CP101 harboring LfD-LDH. In this study, improving the bio-catalytic efficiency by artificial redox self-equilibrium system with a bifunctional fusion protein could reduce the bio-production cost of D-PLA, making this green bio-production of D-PLA a more promising industrial technology.